2013
DOI: 10.1371/journal.pone.0065556
|View full text |Cite|
|
Sign up to set email alerts
|

AIB1 Cooperates with ERα to Promote Epithelial Mesenchymal Transition in Breast Cancer through SNAI1 Activation

Abstract: Epithelial Mesenchymal Transition (EMT) plays a major role in cancer metastasis. Several genes have been shown to play a role in EMT, and one of these is Amplified-in-breast cancer 1 (AIB1), which has oncogenic function and is known to be amplified in breast cancer. However, the role of AIB1 in EMT remains largely undefined at the molecular level. In this study, the effect of AIB1 overexpression on the EMT of the breast cancer cell line T47D was investigated. Overexpression of AIB1 disrupted the epithelial mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 39 publications
1
40
0
Order By: Relevance
“…3). It has also been found that downregulation of the epithelial marker E-cadherin induced the expression of various mesenchymal markers, such as Snail and vimentin, during EMT (25). Consistent with these observations, we found that overexpression of RUNX3 significantly inhibited motility and invasiveness in CRC cells.…”
Section: Discussionsupporting
confidence: 91%
“…3). It has also been found that downregulation of the epithelial marker E-cadherin induced the expression of various mesenchymal markers, such as Snail and vimentin, during EMT (25). Consistent with these observations, we found that overexpression of RUNX3 significantly inhibited motility and invasiveness in CRC cells.…”
Section: Discussionsupporting
confidence: 91%
“…Multiple lines of evidence suggest that different mechanisms are used in SRC-3-mediated cancer cell migration and invasion in a cancer-specific manner (10,11,(27)(28)(29). An inverse correlation between SRC-3 and E-cadherin has been reported in human pancreatic adenocarcinoma, implying that SRC-3 regulates E-cadherin directly or indirectly (27).…”
Section: Discussionmentioning
confidence: 99%
“…An inverse correlation between SRC-3 and E-cadherin has been reported in human pancreatic adenocarcinoma, implying that SRC-3 regulates E-cadherin directly or indirectly (27). By co-activating estrogen receptor α (ERα) in T47D breast cancer cells, SRC-3 also transcriptionally upregulates Snail, which directly represses E-cadherin (28). However, SRC-3 overexpression is not associated with the levels of ERα in UBC tissue samples (10), and urothelial specific ERα-knockout enhanced carcinogen-induced UBC development, suggesting that ERα behaves as a tumor suppressor in UBC (30).…”
Section: Discussionmentioning
confidence: 99%
“…Estradiol also promotes the proliferation of astrocytoma cells through estrogen receptor-α (ERα) and its interaction with AIB1 35. It is the fact that AIB1 interacts with ERα, and subsequently binds to ERα-binding site on the promoter of SNAI1 , a transcriptional repressor for E-cadherin, to promote the transcription of SNAI1 and repress E-cadherin expression, ultimately leading to the initiation and progression of epithelial mesenchymal transition (EMT) 36. Thus, we speculate that specific role and prognostic value of AIB1 amplification in female glioma patients may be related to sex hormones and nuclear receptor levels.…”
Section: Discussionmentioning
confidence: 99%